Interface screening and imprint in poly(vinylidene fluoride/ trifluoroethylene) ferroelectric field effect transistors - Koval, Yury; Lazareva, Irina; Müller, Paul; Müller, Klaus; Schmeisser, Dieter; et al. (Journal of Applied Physics, 2009)
We investigated the imprint effect in ferroelectric capacitors and field effect transistors (FETs) with a poly(vinylidene fluoride/trifluoroethylene) [P(VDF-TrFE)] ferroelectric insulator. The shift in switching voltages and the change in the ferroelectric FET (FeFET) channel conductance were measured as a function of time and the thickness of the ferroelectric layer. Analyzing our experimental data, we show that the imprint originates from interface-induced processes, which effectively screen polarization charges in P(VDF-TrFE). This phenomenon significantly influences the retention of FeFET channel conductance and the memory functionality of FeFET with P(VDF-TrFE). © 2009 American Institute of Physics.